Reactive hemophagocytic Lymphohistiocytosis in systemic lupus Erythematosus-a case report and literature review - Saiful, Tasnuva; Elahi, Quadrat E; Karim, Mostafil; Mostafi, Mamun; Mia, Abdul Ali (Bangladesh Journal of Medicine, 2018)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of immune overstimulation. HLH commonly manifests as multiple organ failure without apparent physiological stress. Primary HLH relates to genetic defects, whereas secondary HLH is triggered by infection, malignancy, or autoimmune disease. This paper describes the features of a young female patient with systemic lupus erythematous (SLE) who presented HLHS as the initial clinical manifestation. Clinical observations: The patient had prolonged fever not associated to an infectious process and did not respond to broad-spectrum antibiotics. Discussion: The diagnosis of HLH secondary to SLE is complicated, because it has some features in common, but HLH is characterized by organomegaly, hyperferritinemia, hypofibrinogenemia, hypertriglyceridemia and cytopenia, a decrease in the erythrocyte sedimentation rate, unlike SLE. An eight week induction therapy with dexamethasone, etoposide, and intrathecal methotrexate increases survival in primary HLH and virus-associated secondary HLH. However, no standardized regimen exists for autoimmune associated HLH. Some patients respond to steroid monotherapy, while refractory patients may require cyclosporin, cyclophosphamide, or tacrolimus. Conclusions: HS can be the initial manifestation of SLE and should be suspected in patients with organ enlargement, cytopenias, clotting disorders, liver disorders and prolonged fever unresponsive to antibiotics. Anakinra may be a treatment option in adult HS associated to SLE. Bangladesh J Medicine Jul 2017; 28(2) : 95-99